Literasi Keuangan Bagi Keluarga Masyarakat Desa Kabufin: Mengapa Penting? - Piter Arson Welay; Yohanes Zefnath Warkula (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2024)
In order to realize public welfare in Indonesia, one of the government's top priorities is financial literacy. The government considers that it will be easier to achieve inclusive development, community welfare and financial system stability through financial literacy. Several people in Kabufin Village, one of the communities in North Aru Sub-district, have lost their jobs due to the COVID-19 outbreak, and the selling price of seaweed has decreased. Therefore, education is needed to improve the community's financial literacy level. Kabufin villagers learned more about financial literacy through this socialization activity, so they can make better financial plans.